2005
DOI: 10.1172/jci200524544
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mouse models of essential tremor: are they essential?

Abstract: The causative genes for essential tremor (ET), one of the most common genetic neurological disorders, have eluded scientists despite intensive search. Two gene loci linked to ET, one on chromosome 3q13 and another on chromosome 2p24.1, have been identified, and a missense mutation in the HS1-BP3 gene on the 2p has been suggested as the cause of the disorder in about 10% of American ET patients. Therefore, the genetic basis for the vast majority of familial ET is still unknown. In this issue of the JCI, the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…These mice exhibit a limb predominant tremor which is absent with relaxation, and is ameliorated by propranolol and primidone, as well as alcohol, hence mimicking ET. However, tremor in these mice appears earlier in life and has a higher mean frequency (19.3 Hz) than the tremor seen in ET patients, and is also accompanied by considerable incoordination, which is not typical for ET (Jankovic & Noebels 2005). The tremor is attributed to the demonstrated loss of GABA‐ergic inhibition of Purkinje cells in the cerebellum and the global reduction of GABA A binding sites in the brain.…”
Section: Essential Tremormentioning
confidence: 77%
“…These mice exhibit a limb predominant tremor which is absent with relaxation, and is ameliorated by propranolol and primidone, as well as alcohol, hence mimicking ET. However, tremor in these mice appears earlier in life and has a higher mean frequency (19.3 Hz) than the tremor seen in ET patients, and is also accompanied by considerable incoordination, which is not typical for ET (Jankovic & Noebels 2005). The tremor is attributed to the demonstrated loss of GABA‐ergic inhibition of Purkinje cells in the cerebellum and the global reduction of GABA A binding sites in the brain.…”
Section: Essential Tremormentioning
confidence: 77%
“…21,22 The first hypothesis is supported by two independent proton MR spectroscopy (MRS) studies that reported a reduced N-acetylaspartate/creatine ratio in patients with ET vs control subjects. 23,24 The latter hypothesis is supported by two lines of evidence.…”
mentioning
confidence: 97%
“…25 Second, a knockout model, mice lacking the gene for the ␣1 subunit of the ␥-aminobutyrate receptors show generalized alcohol-sensitive trembling, like ET. 21,22 Histopathologic data are inconclusive. Qualitative postmortem examinations have revealed no consistent histopathologic abnormalities in small groups of patients with ET, 26,27 yet a quantitative histologic assessment of the cerebellum is still lacking.…”
mentioning
confidence: 99%
“…V C 2013 Wiley Periodicals, Inc. Key words: harmaline; tremor; essential tremor; striatum; electrolytic lesion Essential tremor (ET) is the most frequent movement disorder. Its prevalence varies between 0.4% and 5.6%, although it can affect up to 14% of the population aged 65 years (Elble, 2000;Jankovic and Noebels, 2005). Despite its high prevalence and the fact that it was first described by Most 176 years ago (Most, 1836[see Findley, 2000), there is still a great deal of speculation over the pathophysiological substrate of ET.…”
mentioning
confidence: 99%